2013
DOI: 10.1007/s10661-013-3427-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of urban components on land surface temperature of Istanbul by using remote sensing indices

Abstract: For the past 60 years, Istanbul has been experiencing an accelerated urban expansion. This urban expansion is leading to the replacement of natural surfaces by various artificial materials. This situation has a critical impact on the environment due to the alteration of heat energy balance. In this study, the effect upon the urban heat island (UHI) of Istanbul was analyzed using 2009 dated Landsat 5 Thematic Mapper (TM) data. An Index Based Built-up Index (IBI) was used to derive artificial surfaces in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 45 publications
2
26
0
2
Order By: Relevance
“…Sahana et al investigated the temperature response to land use/land cover using Landsat 5 TM and Landsat 8 OLI data and observed that increase in non-evaporating surfaces and decrease in vegetation had increased the surface temperature in Sundarban Biosphere Reserve, India [22]. Moreover, artificial urban surfaces have been found to have a positive exponential relationship with LST [23]. Quantitative evidence of the effects of land use change on the LST has also been documented [24].…”
Section: Introductionmentioning
confidence: 99%
“…Sahana et al investigated the temperature response to land use/land cover using Landsat 5 TM and Landsat 8 OLI data and observed that increase in non-evaporating surfaces and decrease in vegetation had increased the surface temperature in Sundarban Biosphere Reserve, India [22]. Moreover, artificial urban surfaces have been found to have a positive exponential relationship with LST [23]. Quantitative evidence of the effects of land use change on the LST has also been documented [24].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key possibilities provided by satellite instruments is data acquisition in the thermal infrared (TIR) domain, from which land surface thermal conditions are derived [1][2][3]. Land surface temperature (LST) retrieved from remote sensing data at different scales is an essential variable in environmental research studies, e.g., in agricultural management [4][5][6][7], in urban heat island assessment [8][9][10][11][12], for evapotranspiration (ET) modelling [13][14][15][16][17][18] and drought monitoring [5,6,19].…”
Section: Introductionmentioning
confidence: 99%
“…While it is well understood that imperviousness increases surface temperatures [17,50,51] and that the impervious percentage accounts for most of the LST variation in urban areas [15,18,52,53], very little is known about the situation nearby residential buildings, especially when different urban zones are considered. The knowledge of how the surface temperature nearby residential buildings varies based on the surrounding imperviousness density is very important information that assumes further interest in this study where significant ST_BTFA differences between densely urban and park/rural areas were observed, also revealing different dynamics during daytime and nighttime.…”
mentioning
confidence: 99%